Structure and magnetism of NiFeMnGaxSn1-x (x = 0, 0.25, 0.5, 0.75, 1.00) Heusler compounds - Jace Waybright; Lee Halbritter; Bishnu Dahal; Hanyang Qian; Yung Huh; Pavel Lukashev; Parashu Kharel (AIP Advances, 2019)
The crystal structure and magnetic properties of NiFeMnGaxSn1-x (x = 0, 0.25, 0.50, 0.75 and 1.00) Heusler compounds have been investigated experimentally and theoretically. The computational results suggest that NiFeMnGa0.75Sn0.25 is nearly half-metallic with a spin polarization P of 87%. The bulk samples prepared using arc-melting and annealing exhibit a high degree of Y-type order. All the investigated samples show ferromagnetic spin order with the Curie temperatures ranging from 284 K for NiFeMnGa to 408 K for NiFeMnSn. The intermediate composition NiFeMnGa0.75Sn0.25, which is predicted to be nearly half metallic, has a saturation magnetization of 66.50 emu/g and Curie temperature of 326 K. These results indicate that the NiFeMnGa0.75Sn0.25 alloy has potential for spin-transport-based devices.